Suplementasi Keong Mas (Pomacea canaliculata Lamarck) dalam Ransum Berbasis Limbah Restoran dan Ampas Kelapa terhadap Performa Itik Hibrida - D M Suci; R Mareta; N Y Hidayatulloh; W Hermana (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2019)
This research was aimed to evaluate the effect of boiled golden snail (Pomacea canaliculata Lamarck) supplementation on duck diet based on restaurant waste and coconut pulp to duck performance. A total of 80 Mojosari-Peking hybrid ducks 23 days old were reared for 40 days in this study. The treatments diet was as follows: control diet and 3 treatments diet of boiled golden snail supplementation levels of 10%, 15% and 20%. This research used a completely randomized design with 4 treatments and 4 replicates. All data was analyzed by variance and if there were significantly differences, further analysis applied was a Duncan Multiple Range Test. The variables observed were duck performance (feed consumption, body weight gain and feed conversion ratio) and carcass percentage. The results showed that supplementation of boiled golden snail on diet based on restaurant waste and coconut pulp 10%-20% significantly (p<0.05) increased body weight gain, final body weight, percentage of carcass but decreased feed conversion ratio. It can be concluded that 15% of boiled golden snail (Pomacea canilaculata Lamarck) supplementation on diet based on restaurant waste and coconut pulp can be use as diet of Mojosari-Peking Hybrid duck. Keywords: carcass, golden snail, hybrid duck, performance, Pomacea canilaculata